Molecular characterization of pregnancy-associated breast cancer and insights on timing from GEICAM-EMBARCAM study - Regina Peña-Enríquez; Begoña Bermejo; Marina Pollán; Alejandra Díaz-Chacón; Yolanda Jerez Gilarranz; José J Ponce Lorenzo; Antonio Fernández Aramburo; Blanca Cantos Sánchez de Ibargüen; Ana Santaballa Bertrán; Elena Galve-Calvo; Álvaro Jiménez-Arranz; Yolanda Fernández; et al. (npj Breast Cancer)
Abstract Pregnancy-associated breast cancer (PABC), diagnosed during or shortly after pregnancy, is a challenging entity with an aggressive biology and poor prognosis. This study analyzed the clinicopathological characteristics and gene expression profile of 33 PABC and 26 non-PABC patients using the nCounter BC360 Panel (NanoString). Notably, PABC showed a higher prevalence of basal-like tumors than non-PABC (48.48% vs 15.38%, p = 0.012) and displayed 73 differentially expressed genes (e.g., DEPDC1, CCNA2, PSAT1, CDKN3, and FAM83D), enriched in DNA repair and cell proliferation pathways. Through the PPI network, we also identified a cluster of cell-cycle regulation genes like MYC, FOXM1, or PTEN. Interestingly, differences emerged when comparing patients diagnosed during gestation (PABC-GS) and the postpartum period (PABC-PP), with PABC-PP showing increased expression of immune-related genes, including PD-1, and greater immune cell infiltration (Tregs, macrophages, neutrophils, B-cells). These findings suggest an enhanced proliferative capacity and impaired DNA repair in PABC, and underscore the role of immune infiltration in postpartum cases; providing insights into its aggressive nature and potential targets.